Tradisi Lapeh Kapadi di Masyarakat Minangkabau - Anisa Hayati; Nurman S (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This study aims to determine the community's view of the Lapeh Kapadi tradition in Nagari Simpang, Pasaman Regency. This tradition is an expression of the gratitude from community to Allah Swt for good crops. In the implementation stage there is an assumption that this tradition contains polytheism that is seen from the goat slaughtering event. So it is necessary to see the process of implementing tradition in full and the values contained therein. This type of research is qualitative using descriptive methods. Determination of informants is carried out with purposive sampling. The type of data consists of primary and secondary data, collected through observation, interviews, and documentation. The data validity test is carried out with observation perseverance and triangulation. Data analysis techniques through data reduction, data presentation and conclusions. The results showed that the implementation of the Lapeh Kapadi tradition had several stages and there were values in each of these stages. The values are: religious, gotong royong, friendship and togetherness. These values are prioritized by the people of Nagari Simpang. The limitation of this research is to only look at the process that occurred in 2022 and not in the long period of time. So that there is no comparison of this tradition can survive or not in accordance within the times.